Membudayakan Cium Tangan dan Salaman pada Anak di Sekolah Dasar - Euis Kusumarini; Eka Selvi Handayani; Cindy Swediati Putri; Devi Kurniasari; Maria Fampilia Tea; Sony Christian (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2026)
Cultivating hand-kissing and handshaking habits among students at SDN 004 Samarinda Ilir as a form of character building through religious values, politeness, and respect toward teachers and peers. The research employed a descriptive qualitative method with data collected through observation, interviews, and documentation. The findings reveal that the practice of hand-kissing and handshaking is carried out every morning before learning activities begin and after lessons end. Teachers play an active role as role models, guides, and supervisors in instilling this habit. The positive impacts include improved student respect toward teachers, the growth of a sense of togetherness, and the creation of a more friendly and religious school atmosphere. Challenges faced include the inconsistency of some students, especially in the early grades, in maintaining the habit, which necessitates stronger parental involvement and more intensive collaboration. Thus, the cultivation of hand-kissing and handshaking at SDN 004 Samarinda Ilir has proven effective as a character education strategy that can be continuously preserved.